Liberia : Third Review of Performance Under the Staff-Monitored Program; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the Third Review of Performance Under the Staff-Monitored Program (SMP) on Liberia explains economic developments. The Central Bank of Liberia (CBL) will continue to use the exchange rate to gauge domestic monetary conditions and manage Liberian dollar liquidity to maintain broad exchange rate stability. Progress has been made in rebuilding Liberia's statistical capacity, but more needs to be done to establish the database required for policy formulation and monitoring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet